2020
DOI: 10.1177/0363546520973977
|View full text |Cite
|
Sign up to set email alerts
|

Hip Arthroscopy for Femoroacetabular Impingement in Adolescents: 10-Year Patient-Reported Outcomes

Abstract: Background: Previous studies have demonstrated hip arthroscopy to be an effective treatment for femoroacetabular impingement (FAI) in individuals 18 years of age and older. Long-term outcome data in the adolescent population, however, are limited. Purpose: To report 10-year outcomes after hip arthroscopy in adolescents with symptomatic FAI. Study Design: Case series; Level of evidence, 4. Methods: Prospectively collected data were analyzed on adolescent patients younger than 18 years of age who had hip arthros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 30 publications
7
49
0
Order By: Relevance
“…Collection of PROs may be performed preoperatively and at regular intervals in follow-up. 20 Some commonly used PROs include the modified Harris hip score (mHHS), hip outcomes score (HOS; activities of daily living and sports-specific subscales), nonarthritic hip score (NAHS), and lower extremity functional scale (LEFS); several other PROs are used and could also be considered. Tracking the scores and graphically displaying the results for the patient at selected intervals could be beneficial both in terms of patient education, as well as readiness for return to sport.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
“…Collection of PROs may be performed preoperatively and at regular intervals in follow-up. 20 Some commonly used PROs include the modified Harris hip score (mHHS), hip outcomes score (HOS; activities of daily living and sports-specific subscales), nonarthritic hip score (NAHS), and lower extremity functional scale (LEFS); several other PROs are used and could also be considered. Tracking the scores and graphically displaying the results for the patient at selected intervals could be beneficial both in terms of patient education, as well as readiness for return to sport.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
“…However, there is currently limited medium- and long-term data reporting on the results of arthroscopic treatment for FAIS in adolescents [ 17 , 18 ] and no previous study has selectively reported the outcome in adolescents using the Copenhagen Hip and Groin Outcome Score (HAGOS).…”
Section: Introductionmentioning
confidence: 99%
“…Again, this study did not report nonoperative outcomes. Furthermore, Menge et al 12 reported significant improvements in multiple PROs, including the mHHS (from 56 to 88) at 10 years after hip arthroscopy in a cohort of adolescent patients. This study did not include a nonoperative comparison group but did offer activity modification and physical therapy before surgery.…”
Section: Discussionmentioning
confidence: 99%